Awareness among Intern Doctors about Medical Records and Duty of Doctors in Tertiary Care Hospital, Valsad - Pragnesh Parmar1 , Swapnil Patond2 , Gunvanti Rathod3 , Sudhir Ninave4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background:Optimum knowledge of medical records and duty of doctor is must for every doctor to enhance safe health care delivery in an unbiased standardized way. Present study was undertaken with aim to assess awareness of intern doctors towards medical records and duty of doctors. Materials and methods:Present study was undertaken at Gujarat Medical Education and Research Society (GMERS) Medical College, Valsad, Gujarat after obtaining ethical approval from the Institutional Ethical Committee of Valsad. Total 10 questions were prepared and validated on Likert scale (1 to 5, 1 – Strongly Disagree, 5 – Strongly Agree) regarding medical records and duty of doctors. Total 100 intern doctors of GMERS Medical College, Valsad, Gujarat were subjected to pre-tested and pre-validated Likert scale type questionnaire regarding medical records and duty of doctors after obtaining their informed written consent. Data obtained were analyzed via median score and tabulated. Results:Students were well aware about following facts like Maintenance of patients’ record is legal duty of hospital, Every operation required informed written consent of patient, Fail to attend patient during emergency is punishable, Patient has right to refuse treatment, and Carelessly leaving object into patient body during operation is negligent act. Students were not sure of facts like Patients’ records are property of patients, Refusing patient on religious ground is punishable, Not to treat patient due to HIV is punishable, and doctor has right to choose patient. Students were not aware regarding either doctor can refuse to attend medico-legal case or not. Conclusion: Intern doctors had no awareness regarding duration of preservation of hospital records. Students were not sure of various aspects of medical records and duty of doctors. Compulsory internship in Forensic Medicine subject as well as sensitization workshop regarding medical records and duty of doctors for interns at beginning of their internship may build confidence among them to be aware with various duties of doctors.